EURÍPIDES’ VERSIFICATION AND TEXTUAL CRITICISM - Giangrande, Guiseppe (Myrtia, 2004)
As a modest, but I hope didactically useful, appendix to White’s paper entitled "Two Philological Notes" I should like to underline a methodological criterion which is, alas, not taken into account by many would-be textual critics.